Probability Learning and Aging - Winefield, A. H.; Mullins, G. P. (The Journal of genetic psychology, 1980)
The performance of 48 young (ages 18-20) and 48 old (mean age = 78) adult Ss was studied in a probability learning task which used different reinforcement procedures and material rewards. In the course of learning, the noncorrection procedure was associated with a greater tendency to choose the majority stimulus than was the correction procedure, but this difference was not maintained. All Ss chose the majority stimulus less often than did rats despite the fact that the experimental procedure was based on that used in animal experiments. An interaction effect was found between age level and sex, such that the young women and the old men chose the majority stimulus more than the young men and old women, respectively. It was suggested that the results could imply an increase in rigidity and cautiousness with age in men and a decrease in these qualities with age in women. This suggestion was shown to be consistent with findings reported by other psychologists showing sex differences in personality change associated with aging.